Awareness of COVID-19 infection and mental health screening among medical students - Madhusudhan, Santosh Kumar; Suryaprakash, Harish Kumar; Devendrappa, Srinivas Lokikere (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Novel corona virus disease (COVID-19) has spread throughout the world causing massive morbidity and mortality. The infection has drastically changed the way of living in the current situation. This change has led to higher levels of fear, anxiety and confusion in the minds of the people. The behavior of people influenced by their knowledge and mental status has a huge bearing on the course of COVID-19 pandemic. This study evaluates the awareness of COVID-19 infection and screens the mental health status of medical students of a tertiary care teaching hospital. Methods: This was a cross-sectional, observational survey conducted on an online platform. A predesigned questionnaire was created using google forms and sent to 912 medical students. Ten questions were used to assess knowledge and awareness on COVID-19 and a fear of COVID-19 scale rated on a 5-point Likert was used to screen mental status. Results: 641 students responded to the survey. Almost 95.5% of students lived with their family during the lockdown period. The mean score was 8.15±1.05 for awareness and knowledge. The overall awareness and knowledge of COVID-19 was satisfactory with 81.49% reporting correct answers. Almost 40% of participants were most afraid of COVID-19, 34% became nervous or anxious, watching news and nearly 20% were afraid of losing life because of COVID-19. Conclusions: Currently in the peak of infection, our focus is on reducing transmission and preventing mortality. Managing psychological issue of people, especially healthcare workers is equally important during this pandemic. Enhanced awareness to disease and providing psychological support will allay COVID-19 fears among the people.